2016
DOI: 10.1007/s00266-016-0712-z
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of Forehead, Glabellar, Nasal and Orbital Muscles, and Their Correlation with Distinctive Patterns of Skin Lines on the Upper Third of the Face: Reviewing Concepts

Abstract: This journal requires that authors assign a level of evidence to each submission to which Evidence-Based Medicine rankings are applicable. This excludes Review Articles, Book Reviews, and manuscripts that concern Basic Science, Animal Studies, Cadaver Studies, and Experimental Studies. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors http://www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 12 publications
1
33
0
2
Order By: Relevance
“…Although most individuals share similar anatomy, Abramo and colleagues 13 found 3 distinct dermal insertions for corrugator supercilii, demonstrating that there were 3 distinct shapes for the same muscle. It was suggested that each distinct type of corrugator supercilii caused different eyebrow movements or glabellar lines, which generates distinct patterns of vertical glabellar lines.…”
Section: Discussionmentioning
confidence: 99%
“…Although most individuals share similar anatomy, Abramo and colleagues 13 found 3 distinct dermal insertions for corrugator supercilii, demonstrating that there were 3 distinct shapes for the same muscle. It was suggested that each distinct type of corrugator supercilii caused different eyebrow movements or glabellar lines, which generates distinct patterns of vertical glabellar lines.…”
Section: Discussionmentioning
confidence: 99%
“…3,10 Abramo et al classified four distinct anatomical shapes of the frontalis muscle. 11 In Type I, "full shape", the muscle covers the entire forehead, including the central part, giving rise to parallel wrinkles that extend continuously throughout the forehead ( Figure 1A). Type II is described as "V-shape" and is formed by two bands separated by aponeurotic tissue ( Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1Variation in frontalis anatomy and corresponding forehead line patterns 11. Artwork by Rodrigo Tonan.de Sanctis Pecora Dovepress submit your manuscript | www.dovepress.com DovePress Clinical, Cosmetic and Investigational Dermatology 2020:13…”
mentioning
confidence: 99%
“…In the brow, muscle balance is maintained by the opposition of the only levator, the occipitofrontalis, by the depressor complex including the corrugator supercilii, the procerus, depressor supercilii and the orbicularis oculi. 11 By treating one or both of the depressors and the levator, it is possible to reduce both glabellar and horizontal forehead dynamic wrinkles, to achieve a smooth brow. However, rebalancing of the levator and depressor brow muscles may result in changes in the position and shape of the eyebrows.…”
Section: Introductionmentioning
confidence: 99%